IMPACT OF ASSISTED AND RESISTED SPRINT TRAINING ON SPEED, COORDINATIVE ABILITY, AND STRENGTH IN INTERCOLLEGIATE ATHLETES - Prasad, Jogi; Jesintha, A. Rube (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the impact of assisted and resisted sprint training on speed, coordinative ability, and strength in intercollegiate athletes. Sprinting, a fundamental skill for athletes across various sports, demands a combination of strength, coordination, and speed. The paper examines the physiological effects of assisted sprint training (which involves devices or techniques to increase speed, such as downhill running or tethered sprinting) and resisted sprint training (which includes uphill running, sleds, or resistance bands to create an opposing force). The study delves into how assisted sprint training enhances stride length, power output, and acceleration, contributing to improved maximal speed. It also highlights the role of resisted sprint training in enhancing strength, muscle recruitment, and force production, which translates to better sprinting performance over longer distances and increased power during acceleration phases. Furthermore, the review addresses the influence of these training methods on the coordinative abilities of athletes, such as balance, rhythm, and body control while sprinting. These components are essential in optimizing an athlete's performance and reducing the risk of injuries. The paper concludes by suggesting that combining both training methods can provide a holistic approach to improving speed, strength, and coordination, offering a competitive edge to intercollegiate athletes in track and field, football, and other speed-dependent sports. The paper calls for further research to explore long-term effects and optimal training protocols for diverse athlete profiles.